2020
DOI: 10.1111/1742-6723.13540
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical features of emergency department patients with suspected COVID‐19: Initial results from the COVID‐19 Emergency Department Quality Improvement Project (COVED‐1)

Abstract: the COVED Project demonstrates that the rapid establishment of an agile clinical registry for emergency care is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 8 publications
4
35
1
Order By: Relevance
“…Actually, patient-specific medical decisions and interventions are necessary in these scenarios [ 27 ]. In line with the findings of this study, other researchers have also emphasized on promoting and monitoring the quality of intensive care [ 25 ] and the regular updating of health care guidelines [ 28 ] for these patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Actually, patient-specific medical decisions and interventions are necessary in these scenarios [ 27 ]. In line with the findings of this study, other researchers have also emphasized on promoting and monitoring the quality of intensive care [ 25 ] and the regular updating of health care guidelines [ 28 ] for these patients.…”
Section: Discussionsupporting
confidence: 85%
“…It was found that the patients also had special care needs such as suctioning pulmonary secretions, frequent checking on vital signs, and ventilation. Patients with COVID-19 represent symptoms such as cough, dyspnea, fever, sore throat, and sometimes other nonspecific presentations; nevertheless, only 5% of these patients will require ventilation [ 25 , 26 ]. In patients with severe symptoms, in addition to ventilation, monitoring and maintaining the function of several vital organs such as the heart and kidneys, as well as extremities (legs and fingers) are very important.…”
Section: Discussionmentioning
confidence: 99%
“…The higher frequency of symptoms could suggest that those patients visited the ED earlier; however, in our sample, patients with headache presented to the ED later than those without headache. This could reflect that patients without headache suffer from a more severe case of COVID-19 and therefore they seek medical attention earlier [24].…”
Section: Discussionmentioning
confidence: 99%
“…During the first month of SOE measures, the number of patients diagnosed with COVID-19 at both sites was low. 13 Adult patients presenting to AH or SH ED during the study period were included. Patients were excluded if they were transferred from another hospital or had a positive SARS-CoV-2 swab result during their ED encounter.…”
Section: Methodsmentioning
confidence: 99%